Analisis implementasi manajemen risiko dalam perbankan digital: Tantangan era teknologi finansial - Indriaputri, Rahmaniyah (Maliki Interdisciplinary Journal, 2025)
Digital banking in Indonesia faces complex risk dynamics due to the development of financial technology. The purpose of this study is to examine various approaches to implementing risk management in the face of threats such as problematic financing risks, market volatility, and liquidity pressures. The study, which uses a descriptive-qualitative approach based on literature review, finds that analytical technology, enhanced cybersecurity, and improved risk culture are the primary ways to mitigate damage to digital banks. Competition from fintech, changes in consumer behavior, and the need to adapt to new regulations are major challenges. The research findings indicate that to maintain financial system stability and customer trust, technological innovation and mature risk management must work in tandem. In the future, the success of digital risk management implementation will depend on enhancing human resources and risk culture.